2006
DOI: 10.1038/sj.bjc.6603056
|View full text |Cite
|
Sign up to set email alerts
|

Remission from Kaposi's sarcoma on HAART is associated with suppression of HIV replication and is independent of protease inhibitor therapy

Abstract: Highly active antiretroviral therapy (HAART) reduces the incidence and improves the prognosis of Kaposi's sarcoma (KS). This study was designed to identify factors associated with KS clinical responses in HIV-infected patients during HAART. We reviewed the files of 138 HIV-1-infected patients with KS. Epidemiologic and HIV-related clinical and biological parameters were recorded at KS diagnosis (baseline) and every 6 months thereafter. In a subset of 73 antiretroviral-naive patients, we compared the clinical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
1
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 42 publications
3
61
1
5
Order By: Relevance
“…Infection with this virus is a necessary condition, but it is not sufficient alone to cause KS, highlighting how genetic and angiogenic factors and the production of several inflammatory cytokines play a role in the multistep pathogenesis of KS [4] . As KS can be considered to be an opportunistic tumour, the restoration of immune competence is associated with remission in organ transplant recipients [5] and in acquired immune deficiency syndrome (AIDS)-related KS [6] . In classic KS, the cause of the underlying immunodeficiency is more difficult to identify and therefore to target by treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Infection with this virus is a necessary condition, but it is not sufficient alone to cause KS, highlighting how genetic and angiogenic factors and the production of several inflammatory cytokines play a role in the multistep pathogenesis of KS [4] . As KS can be considered to be an opportunistic tumour, the restoration of immune competence is associated with remission in organ transplant recipients [5] and in acquired immune deficiency syndrome (AIDS)-related KS [6] . In classic KS, the cause of the underlying immunodeficiency is more difficult to identify and therefore to target by treatment.…”
Section: Introductionmentioning
confidence: 99%
“…KS regression and HIV suppression may also be achieved using non-PI-based HAART regimens [ 261 ]. Moreover, persistent or de novo KS was also reported in clusters of AIDS patients with high CD4+ T-lymphocyte counts and low or undetectable HIV-1 viremia [ 224 , 266 ], indicating that some patients may experience effective HIV-1 suppression and restoration of immune function not accompanied by KS remission.…”
Section: Epidemic Kaposi's Sarcomamentioning
confidence: 99%
“…Indinavir inhibited matrix metalloprotease 2 (MMP-2) proteolytic activation and angiogenesis in a hepatocellular carcinoma model [24]. However, a recent retrospective analysis of 138 patients with AIDS-associated KS showed that the response to KS was not associated with the type of HAART regimen used [25]. Undetectable HIV viral load was strongly associated with KS remission, while CD4 cell count was not.…”
Section: Immune Reconstitution and Antiviral Therapymentioning
confidence: 99%